Internet connectivity disruption in Cambodia (Cambodia) - Voidly (2026)
CRITICAL severity disruption detected in Cambodia. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: KH-2026-0030
Keywords: internet disruption; KH; disruption; critical